No repique do agogô, na batida do atabaque: perspectivas para o ensino de História desde as epistemologias de terreiro - Correia, Carlos Marley Mateus (2024)
Based on this research, I propose an investigation of the possibilities surrounding the use of Candomblé Ketu ringtones as a teaching resource for History Teaching, from the processes of construction, preservation and mediation of knowledge in Terreiros de Candomblé. Understanding that the School and the Terreiro comprise training spaces, I reflect on the possibilities of intertwining between the educational processes of these territories. I organize the work into three general points, going from a broader perspective and sharpening the view throughout the research. I discuss the specificities of the School and the Terreiro, observing divergences and convergences between these spaces, the legal supports that, in a context of epistemic and religious racism, guarantee and protect the importance of dialogue between the school institution and Afro-religious communities. I also present the debates surrounding the Teaching of History and the knowledge developed since Terreiro, reflecting on the possibilities of understanding Candomblé rhythms as historical sources. Finally, I provide an analysis of the touches themselves and their uses in a school context. I argue, in general terms, that the touches played on drums constitute a system of preserving the memory of ancestors worshiped in terreiro communities, making it possible to perceive from this musicality a set of aspects inherent to these ancestors. I propose as a pedagogical product the implementation of workshop classes, in which students have contact with the musical materiality of the terreiro, based on the musical instruments used, such as atabaques and agogôs, as well as with the percussive rhythms dedicated to specific orixás. I participate in the construction of the research and the elaboration of the workshop class with authors such as Beatriz Nascimento, Vanda Machado, Leandro Bulhões, wanderson flor do natal, Denise Botelho, Luiz Antônio Simas and Muniz Sodré